PENGARUH KEPERCAYAAN, FITUR LAYANAN, KEMUDAHAN, DAN KEAMANAN TERHADAP KEPUTUSAN MENGGUNAKAN MOBILE BANKING DI KALANGAN GENERASI-Z - Rumuar, Anafiah; Nugroho, Hendrato Setiabudi (STIE Mahardhika, 2024)
The banking sector in Indonesia is undergoing substantial growth, with mobile banking services emerging as a key innovation. BRImo, a service provided by PT Bank Rakyat Indonesia, enables users to access banking services remotely, reducing the need for teller or customer service assistance. This study aims to examine the impact of trust, features, convenience, and safety on Generation-Z's decision to adopt mobile banking. A quantitative approach was employed, with primary data collected via questionnaires. The sample comprised 100 students from the top five universities in Yogyakarta, selected through purposive sampling. Data analysis was conducted using SPSS 25. The findings reveal that trust, features, convenience, and safety significantly influence Generation-Z's decision to use mobile banking, both individually and collectively. The study concludes that each of these factors—trust, features, convenience, and safety—has a significant partial effect, while their combined influence is also substantial in shaping Generation-Z’s decision to adopt mobile banking services.